Differential regulation of two Ca(2+) influx systems by pheromone signaling in Saccharomyces cerevisiae - Muller, E M; Locke, E G; Cunningham, K W (Genetics (Austin), 2001)
The budding yeast Saccharomyces cerevisiae generates calcium signals during the response to mating pheromones that promote survival of unmated cells. A Ca(2+) channel composed of Cch1p and Mid1p was previously shown to be necessary for the production of these calcium signals. However, we find that the Cch1p-Mid1p high-affinity Ca(2+) influx system (HACS) contributes very little to signaling or survival after treatment with alpha-factor in rich media. HACS activity was much greater after calcineurin inactivation or inhibition, suggesting the Cch1p-Mid1p Ca(2+) channel is subject to direct or indirect regulation by calcineurin. Instead a distinct low-affinity Ca(2+) influx system (LACS) was stimulated by pheromone signaling in rich medium. LACS activity was insensitive to calcineurin activity, independent of Cch1p and Mid1p, and sufficient to elevate cytosolic free Ca(2+) concentrations ([Ca(2+)]c) in spite of its 16-fold lower affinity for Ca(2+). Overexpression of Ste12p or constitutive activation of this transcription factor in dig1 dig2 double mutants had no effect on LACS activity but stimulated HACS activity when calcineurin was also inactivated. Ste12p activation had no effect on Cch1p or Mid1p abundance, suggesting the involvement of another target of Ste12p in HACS stimulation. LACS activation required treatment with mating pheromone even in dig1 dig2 double mutants and also required FAR1, SPA2, and BNI1, which are necessary for proper cell cycle arrest and polarized morphogenesis. These results show that distinct branches of the pheromone-signaling pathway independently regulate HACS and LACS activities, either of which can promote survival during long-term responses.